Charge pumping test technique using CMOS ring oscillator on leakage issue. (October 2017) - Liu, Yongbo; Zhu, Zhengyong; Zhu, Huilong; Wan, Guangxing; Li, Junfeng; Zhao, Chao
Abstract: With the scaling down of CMOS devices, traditional charge pumping measurement used to extract interface trap distribution is confronted with great challenge due to large leakage current. Special pulses with high frequency and short transition time are required to accurately extract the interface trap density, which places great demands on equipments in current charge pumping measurements. In this paper, a new charge pumping test technique is proposed, in which suitable voltage pulses are produced by CMOS ring oscillator instead of equipments. Simulation results show that frequency of the voltage pulses generated by ring oscillator can be readily greater than 1 GHz, and rising/falling time is around 60 ps. Due to these superiorities, new technique can measure interface trap density more exactly by totally eliminating the influence of gate leakage without any handling with the leakage current.